Longitudinal study of habits leading to malocclusion development in childhood - Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Artênio José Ísper [UNESP]; Chaves Lima, Arinilson Moreira [UNESP]; Lolli, Luiz Fernando [UNESP]; Saliba, Orlando [UNESP]; Garbin, Clea Adas Saliba [UNESP] (Biomed Central Ltd, 2014)
Background: The increased prevalence of malocclusions represents a secular trend attributed to the interaction of genetic and environmental factors. The analysis of factors related to the causes of these changes is essential for planning public health policies aimed at preventing and clinically intercepting malocclusion. This study investigated the sucking habits, nocturnal mouth breathing, as well as the relation of these factors with malocclusion.Methods: This is a longitudinal study in which 80 mother-child pairs were monitored from the beginning of pregnancy to the 30th month after childbirth. Home visits for interviews with the mothers were made on the 12th, 18th and 30th months of age. Finger sucking, pacifier sucking, bottle feeding, breastfeeding and nocturnal mouth breathing, were the variables studies. On the 30th month, clinical examinations were performed for overjet, overbite and posterior crossbite. A previously calibrated single examiner (Kappa coefficient = 0.92) was responsible for all examinations. Data were analyzed using the chi-squared or Fisher's exact tests, at a significance level of 5%.Results: Bottle feeding was the most prevalent habit at 12, 18 and 30 months (87.5%; 90% and 96.25%, respectively). Breastfeeding was 40%, 25% and 12.50% at 12, 18 and 30 months, respectively. Nearly 70% of the children in this study had some sort of malocclusion. Pacifier sucking habit at 12, 18 and 30 months of age was associated with overjet and open bite; and at 30 months, an association with overbite was also observed. Finger sucking habit and breastfeeding at 12, 18 and 30 months were also associated with overjet and open bite. The posterior crossbite was associated with bottle feeding at 12 and 30 months, and nocturnal mouth breathers at 12 and 18 months.Conclusions: Sucking habits, low rates of breastfeeding, and nocturnal mouth breathing were risk factors for malocclusion.
Keywords: Oral health; Malocclusion; Infant; Longitudinal studies